Design optimization of office chair star base leg using product LCM and anisotropic material properties from injection moulding simulation. (2021) - Ganesh Rajkumar, N.; Adam Khan, M.; Rajesh, S.; Faris, Waleed F.
Abstract: The aim of this research is to design the office chair leg component through Product LCM using anisotropic material. For every product, Product Life Cycle Management (PLCM) plays a vital role to satisfy the customers requirement; especially on weight factor, the cost, failure rate, Time to market, manufacturing feasibility and aesthetics. The anisotropic material properties are mapped from the injection molding machine package to the software on elemental mesh analysis. In a recent time number of researchers used the injection molding simulation software interface with Finite element analysis software to predict the anisotropic material property induced during the molding process. The analysis of the office chair leg is done with respect to the BIFMA ×5.1 office chair standard. Since the leg must withstand both the bending and torsion load induced due to various caster position, the usage of anisotropic material properties plays a significant role in evaluating its stiffness. ANSYS is used for the structural evaluation, Altair OptiStruct is used for Topology optimization and Moldex3D is used for simulating the injection molding process. The leg is optimized from its concept design and validated in FEA using the process induced anisotropic material properties instead of using the isotropic properties available in the material datasheet. The optimum leg design is achieved, which is passing the stress criteria with the factor of safety.